Language Learning Motivation among Senior High School Students - Bhuana, Gartika Pandu (LPPM Universitas Advent Indonesia, 2017)
Abstract Motivation is one of main determinant factor in learning second or foreign language. There are two types of motivation, which are integrative and instrumental motivation. Both of them play an essential role of the success in learning second or foreign language. Unfortunately, there is some debate about which kind of motivation is important for second language learner. Therefore, the aim of this study is to investigate the senior high school students’ motivation toward learning English as a second language. The study is quantitative design. The participant of this study was twelve grade students at one of senior high school in Bandung. The data were obtained through questionnaire. The used questionnaire was integrative and instrumental motivation scale of Gardner’s Attitude/Motivation Test Battery (AMTB) that is adapted by Vaezi (2010). The questionnaire has 5-point scale ranged from “strongly disagree” to “strongly agree”. The data gained then was analyzed using SPSS 16.0. The result of the study showed that senior high school students were instrumentally motivated in learning English as a second language. In their point of view, learning English was important for supporting their future job and career. Keywords: Integrative and instrumental motivation, senior high school students